Dedication to Pan from the Pantikapaion Suburbs - Belik, Yuri; Kucherevskaya, Nina; Pavlichenko, Natalia (Hyperboreus, 2024)
In 2022, a marble block was accidentally found in Kerch. Its surface was covered with a layer of opus signinum and brown algae. One of its sides had a plain square hollow with two drains. These features indicate that the block was used as a building material for some hydraulic structure. After a set of restoration measures, an inscription with partially preserved text was uncovered on one of the block edges. The inscription reads: “[- -]os, Praxilaos, (the sons of) Kleodoros (?), the Mantineians dedicated to Pan, during the times of Paerisades, the archon of Bosporus and Theodosia, reigning over the Sindoi, all the Maeotai, Thatoi”. Judging by the hollow on the block’s upper edge, it was a pedestal for a stone statue. The inscription is dated back to the 330s–310s BC. This is a votive offering by two Mantineians who probably were mercenaries in the army of Paerisades I. They made a dedication to Pan either as one of the supreme deities of their motherland Arcadia or, more likely, due to his ability to inspire divine terror in enemy troops. There was no individual cult of Pan in Bosporus; however, he could be worshiped together with the nymphs or the deities of the Dionysian circle.